Tri Agung Bhaktiar., S.Kep Pengaruh Pemberian Madu Murni Terhadap Frekuensi Bab Dan Konsistensi Feses Pada Anak Diare Di Wilayah Rw 05 Kelurahan Srengseng Kecamatan Kembangan Jakarta Barat: Sebuah Penelitian Kuasi-Eksperimen di Lingkungan Komunitas - Bhaktiar , Tri Agung; Trianingsih , Devi; Ramadhan , Gaung Eka; Yatnikasari , Aat (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Diarrhea is a common health issue in children that may cause dehydration and growth disturbances. This study aimed to determine the effect of pure honey on bowel movement frequency and stool consistency in children with diarrhea. Methods: This quasy experiment study used a one-group pretest-posttest design involving 20 children selected through purposive sampling. Data collection tools included observation sheets and the Bristol Stool Chart. The intervention was conducted over several days following the research protocol.. Results: The average frequency of bowel movements decreased from 5.90 to 2.20 times per day, while stool consistency improved from types 6–7 to types 3–4. Statistical analysis using the Wilcoxon Signed Rank Test showed significant results, with a p-value of 0.000 for both variables. Conclusion: The antibacterial, anti-inflammatory, osmotic, and enzymatic properties of pure honey, such as flavonoids and glucose oxidase, contribute to digestive recovery. Pure honey can be considered an effective non-pharmacological intervention to reduce symptoms of diarrhea in children.